IMPLEMENTASI UU NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN BAGI TENAGA KERJA PEREMPUAN DI KABUPATEN PURBALINGGA - Bintoro, Rahadi Wasi; Ardhanariswari, Riris; Permana, Rahman (Jurnal Dinamika Hukum, 2008)
The governmental intervention through law and regulation have brought the elementary change in labour relationship, namely the nature of private and public, so that regulation thet released by government have in such a way broadness, not only in law aspect which relate with the job, but also before and after labour relationship. This concept have accommodated in Law Number 13 Year 2003 about labourness. Law No. 13 Year 2003 have given the arrangement about the protection of law for woman labour, such as the protection of law for underage woman labour, the protection of law for pregnant woman labour and the protection of law in the case of in working and take a rest. But in the other hand, in Law No. 13 Year 2003, there are weakness in giving protection for woman labour. Based on Article 10 sentence (1) and (3) Law No. 32 year 2004 about Local Governance, that besides political business abroad, defender, security, yustisi, fiscal and national monetary, and also religion become the business of local government. For the reason, Local government can release the furthermore regulation such as local regulation and also regent decree, utilize to arrange furthermore about labourness. Kata kunci : tenaga kerja, perusahaan, perlindungan hukum